PENGARUH KOMPENSASI DAN KEPUASAN KERJA TERHADAP KINERJA GURU DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING - Afghoni, Muhammad Nur Jamaluddin Al; Wahyudi, Amin - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2011)
ABSTRACT The purpose of this research is to analysis effect: (1) compensation to the teacher performance of SD Kampus Kuripan Purwodadi at Grobogan, (2) job satisfaction to the teacher performance of SD Kampus Kuripan Purwodadi at Grobogan, (3) organization commitment to the teacher performance of SD Kampus Kuripan Purwodadi at Grobogan, (4) intervening effect of commitment organization to correlation between compensation and job satisfaction to the teacher performance of SD Kampus Kuripan Purwodadi at Grobogan. Populations in this research are teachers of SD Kampus Kuripan Purwodadi at Grobogan as many as 42 persons, amount of sample is 42 persons with total sampling method. The conclusion of this research: (1) Hypothesis: â€œThe compensation has significant effect to the teacher performance of SD Kampus Kuripan Purwodadi at Groboganâ€ is true, (2) Hypothesis: â€œThe job satisfaction has significant effect to the teacher performance of SD Kampus Kuripan Purwodadi at Groboganâ€ is not true, (3) Hypothesis: â€œorganization commitment has significant effect to the teacher performance of SD Kampus Kuripan Purwodadi at Groboganâ€ is true, (4) Hypothesis: â€œThe commitmen organization mediate effect of compensation and job satisfaction to the teacher performance of SD Kampus Kuripan Purwodadi at Groboganâ€ is non true. Keywords: compensation, job satisfaction, organization commitment, employee performance